Evaluation of the development of Acute Kidney Injury in patients interned in the ICU of a hospital in the midwest of Santa Catarina (Research, Society and Development, 2023)
Acute kidney injury (AKI) is the sudden loss of kidney function over a period of time, generating an accumulation of substances such as urea and creatinine, with or without decreased diuresis. The present study analyzed the incidence and clinical status of patients who developed ARF during their stay in an ICU at a hospital in the midwest of Santa Catarina. The methodology consisted of carrying out a data survey with a quantitative approach, through the analysis of data collected from the ICU's medical records. From the analysis of 77 medical records, it was found that 15.58% of hospitalized patients evolved with ARI. Of the patients affected by ARI, 83.33% were male and 16.67% female, the prevalent age group was 51 to 55 years, in addition to the elderly, aged over 60 years. Regarding mortality, 91.67% died. The risk factors found in the patients were the length of stay in the unit, previous illnesses and reasons for hospitalization due to cardiac, pulmonary and surgical pathologies, in addition to nephrotoxic drugs and age. It is essential that more cautious measures and greater resources be made available.